Revisiting the Philippine Assembly of 1907 profiles and political careers of Bikolano Assemblymen - Totanes, Stephen Henry S. (2008)
This paper revisits the Philippine Assembly of 1907 by focusing on the profiles and political careers of the eight delegates form the region known as Kabikolan. Their careers will be reviewed in the context of the careers of the more prominent delegates of this Assembly ? Sergio Osmeña of Cebu and Manuel Quezon of Tayabas, the elected Speaker and Majority Floor Leader, respectively, of the Assembly. The study concludes that it was really the personae of these delegates that were truly represented to a wider Manila-based audience, and not so much the interest of their local constituents in Kabikolan.
Includes bibliographical references (pages 305-309).